Dublin’s saltmarshes contain climate-relevant carbon pools - Burke, Shannon A.; Manahan, Jane; Eichelmann, Elke; Cott, Grace M. (Frontiers in Marine Science, 2022)
Wetland ecosystems, particularly coastal vegetated ecosystems, play a vital role in climate mitigation and adaptation. Coastal vegetated habitats (including coastal wetlands such as seagrass meadows, saltmarshes, and mangroves) are some of the most efficient ecosystems for storing carbon on a per area basis—retaining organic carbon for centuries to millennia. We conducted carbon stock assessments, to a depth of 1 m, across four young saltmarsh sites and the adjacent mudflats in Dublin, Ireland. Soil cores and vegetation samples were taken across each site in order to analyse the carbon content of each carbon pool. The areal carbon density of Dublin's saltmarshes were determined to be 112.13 ± 10.10 Mg Corg ha-1. The soil carbon pool of these saltmarshes contribute 87% to the total carbon stock, with living plant biomass contributing the remaining 13%. These saltmarshes are areas of active accretion and their degradation will lead to the loss of climate-relevant carbon pools.